Calidad de vida de los pacientes con enfermedad pulmonar obstructiva crónica mediante la aplicación del cuestionario saint george respiratory, en el Hospital General Martin Icaza, Babahoyo Los Ríos, octubre 2018- abril 2019 - Alvarado Avilez, Lenin (2019)
Summary. COPD is a disease that is characterized by obstruction of the respiratory tract by emphysema and chronic bronchitis. The first trigger is cigarette smoking at an early age, it is estimated that COPD deaths worldwide increase more than 30% in the next 10 years and is the third cause of death (WHO). Objective. It is to educate and propose to patients that there is an alternative for the improvement of their disease where we would evaluate their quality of life in order to be the great start of a pulmonary rehabilitation treatment to follow. The methodology. A descriptive, cross-sectional field study was carried out through the analytical method with a qualitative and quantitative approach. The universe of the Martin Icaza hospital study in the Babahoyo canton is 50 people. Simple random sampling was used. The interview technique and the survey technique were applied to gather information. The results. We can determine that 86% of the patients surveyed were totally unaware of the quality of life, being a serious problem for these people, since their recovery is based both physically and emotionally. The results obtained 60% still continue with the consumption of the cigarette, the severity of the symptoms of COPD will depend on the magnitude of the damage to the lungs, if you continue smoking the damage will worsen faster than if you stop doing it, and thus increase the limitations It was concluded that 84% of these patients agree to implement the Saint George Respiratory questionnaire. It concludes. That the index is high of these patients because having such a dangerous disease they continue with the consumption of tobacco by 60% and by not knowing alternatives for the improvement of their disease it is worrisome that it is 86%. The results obtained allow the fulfillment of the objectives and the verification of the hypothesis.